Accretion-induced prompt black hole formation in asymmetric neutron star mergers, dynamical ejecta, and kilonova signals. Issue 2 (27th June 2020) - Bernuzzi, Sebastiano; Breschi, Matteo; Daszuta, Boris; Endrizzi, Andrea; Logoteta, Domenico; Nedora, Vsevolod; Perego, Albino; Radice, David; Schianchi, Federico; Zappa, Francesco; Bombaci, Ignazio; Ortiz, Nestor
ABSTRACT: We present new numerical relativity results of neutron star (NS) mergers with chirp mass 1.188 M⊙ and mass ratios q  = 1.67 and q  = 1.8 using finite-temperature equations of state (EOS), approximate neutrino transport, and a subgrid model for magnetohydrodynamics-induced turbulent viscosity. The EOS are compatible with nuclear and astrophysical constraints and include a new microphysical model derived from ab initio calculations based on the Brueckner–Hartree–Fock approach. We report for the first time evidence for accretion-induced prompt collapse in high-mass-ratio mergers, in which the tidal disruption of the companion and its accretion on to the primary star determine prompt black hole (BH) formation. As a result of the tidal disruption, an accretion disc of neutron-rich and cold matter forms with baryon masses ∼0.15 M⊙, and it is significantly heavier than the remnant discs in equal-masses prompt-collapse mergers. Massive dynamical ejecta of the order of ∼0.01 M⊙ also originate from the tidal disruption. They are neutron-rich and expand from the orbital plane with a crescent-like geometry. Consequently, bright, red, and temporally extended kilonova emission is predicted from these mergers. Our results show that prompt BH mergers can power bright electromagnetic counterparts for high-mass-ratio binaries, and that the binary mass ratio can be, in principle, constrained from multimessenger observations.